KONTEKSTUALISASI NILAI-NILAI PENDIDIKAN SPIRITUAL TERHADAP PENGUATAN BUDAYA ASSIDDIANG MASYARAKAT BUGIS KAMPUNG GURU PINRANG - Mardia Mardia (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2017)
CONTEXTUALIZATION OF SPIRITUAL EDUCATION VALUES IN STRENGTHENING "ASSIDDIANG" CULTURE COMMUNITY OF BUGIS "KAMPUNG GURU PINRANG". This study aimed to describe the characteristics and contextualization of education spiritual values on strengthening Assiddiang culture as Local Wisdom in the perspective of Islamic practice Bugis community at Kampung Guru Pinrang. This study was categorized as field research with descriptive qualitative-naturalistic approach and case studies. The data were analysed using interactive model analysis proposed by Miles and Huberman: data reduction, data display, conclusions and verification. The results showed that the spiritual education values practiced by Bugis community have strengthened their Assiddiang culture (unity). Assiddiang culture is identified as local wisdom in the Islamic practice Bugis community Kampung Guru. This culture has been internalized so this values system internalization needs to be maintained and has contributed to the planting of the value and character of social change, especially in Bugis community and Indonesian people in general.